ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRESTASI KERJA GURU SMP (Studi Kasus Guru SMP di Kecamatan Pillau Dullah Utara Kota Tual) - Rismawati Rismawati (AkMen JURNAL ILMIAH, 2018)
The purpose of this research is to know the influence of compensation, work discipline and work environment to the achievement of private junior high school teachers in Pillau Dullah North District Tual City. The population in this research is Private Junior High School Teachers in District Pillau Dullah Utara Tual City with total sample of 66 people. Methods in collecting data in this study are questionnaires, interviews, and documentation. Methods of data analysis using descriptive method and quantitative method that is by multiple linear regression analysis used to measure Influence of Compensation, Work Discipline and Work Environment To Work performance of Private Junior High School Teacher in District of Pillau Dullah North of Tual City. Based on the F test the independent variables (compensation, motivation and work discipline) together have a positive and significant influence on the dependent variable (teacher work performance). By testing the correlation coefficient (R) obtained that the level of correlation or the relationship between compensation, motivation and work discipline on teacher work performance is a high relationship that is 72.1%. And motivation is the most dominant factor affecting Teacher performance of Private Junior High School in District Pillau Dullah North Tual City.